Framework Analysis of Smart House based on Orange Technology use Systematic Literature - Sudrajat, A.; Handoko, Melyani; Zahra; Kurniawan, Hendra; Solehudin, Didin; Sari, Dian Indah; Sumantri, Fazhar (Journal of Management and Informatics, 2025)
Now days, the home environment is still much  less supportive of life for the elderly, most elderly living at  home need a companion to help them. Safety, health, happiness  and independence will be difficult for them to get even the  elderly will be further away from the surrounding  environment. Based on population projection 2017 data there  are 23.66 million elderly people in Indonesia and predicted in  2020 there are 27.08 million people elderly. Smart homes that  are currently widely studied have not focused on elderly; most  smart homes only provide a sense of security and convenience  for adult residents. And this will be a problem that until now  has not solved the improvement of human life through  technology to get happiness, care and health especially for the  elderly. In many cases of the elderly, it is easier to send them to  live in a nursing home and that keeps them separated from  their families for the rest of their lives. That's what makes  them less happiness. Orange Technology is a collection of  technological elements to improve human life by getting  happiness, Care and health. This study reviewed the journals  of scientific databases such as IEEE explore, ACM digital  library and Proquest published from 2002 to 2017. From the  search results obtained 54 papers that will answer the scientific  questions of this research. The result of this research is a  framework of smart house that has Sensor, Monitoring,  Wireless, Scalability, Low cost, GPS and ease of installation  and maintenance as components of smart house of orange  technology for elderly.